Tissue Engineering - Wernscheid ,Verena (Universitèatsverlag Gèottingen, 2012)
Tissue engineering, the creation of human tissue in the laboratory by the use and propagation of human cells to develop commercial products, faces many problems concerning its legal regulation. There have been numerous alterations to the laws governing biotechnology